2007
DOI: 10.3727/000000007783464768
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cell Transplantation Improves Reticulospinal Axon Growth and Forelimb Strength after Severe Cervical Spinal Cord Contusion

Abstract: Schwann cell (SC) implantation alone has been shown to promote the growth of propriospinal and sensory axons, but not long-tract descending axons, after thoracic spinal cord injury (SCI). In the current study, we examined if an axotomy close to the cell body of origin (so as to enhance the intrinsic growth response) could permit supraspinal axons to grow onto SC grafts. Adult female Fischer rats received a severe (C5) cervical contusion (1.1 mm displacement, 3 KDyn). At 1 week postinjury, 2 million SCs ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 156 publications
3
53
1
Order By: Relevance
“…Plastic embedment of a 2-mm-long piece of spinal cord containing the lesion was prepared as described previously (Pearse et al 2005). With the use of Stereoinvestigator software (MicroBrightfield), the total number of myelinated axons in the area corresponding to the RST in the white matter across from the lesion was stereologically quantified (Schaal et al 2007). Calculations were performed on three 1-m plastic toluidine bluestained semithin transverse sections taken from the injury epicenter within the tissue block.…”
Section: Methodsmentioning
confidence: 99%
“…Plastic embedment of a 2-mm-long piece of spinal cord containing the lesion was prepared as described previously (Pearse et al 2005). With the use of Stereoinvestigator software (MicroBrightfield), the total number of myelinated axons in the area corresponding to the RST in the white matter across from the lesion was stereologically quantified (Schaal et al 2007). Calculations were performed on three 1-m plastic toluidine bluestained semithin transverse sections taken from the injury epicenter within the tissue block.…”
Section: Methodsmentioning
confidence: 99%
“…Only two studies that evaluated adult nervederived rodent SCs were performed at the cervical level of the spinal cord. One study that used a clinically relevant contusion injury without co-treatments reported improvements in forelimb grip strength and forelimb hang tests (Schaal et al, 2007).…”
Section: Behaviormentioning
confidence: 99%
“…Every fourth section was mounted onto a series of five slides. One series was used for immunohistochemical staining with the neuron-specific marker NeuN to permit stereological quantification of neuron numbers according to previously described methods (Schaal et al, 2007). After removing the paraffin from the sections, they were rehydrated through a series of xylene and ethanol exposures.…”
Section: Histological Assessmentmentioning
confidence: 99%